Serum level of calpains product as a novel biomarker of acute lung injury following cardiopulmonary bypass - Yi, Chenlong; Chen, Fangyu; Ma, Rongrong; Fu, Zhi; Song, Meijuan; Zhang, Zhuan; Chen, Lingdi; Tang, Xing; Lu, Peng; Li, Ben; Zhang, Qingfen; Song, Qifeng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: The aim of this study was to test the hypothesis whether serum level of calpains could become a meaningful biomarker for diagnosis of acute lung injury (ALI) in clinical after cardiac surgery using cardiopulmonary bypass (CPB) technology. Methods and results: Seventy consecutive adults underwent cardiac surgery with CPB were included in this prospective study. Based on the American-European Consensus Criteria (AECC), these patients were divided into ALI (n = 20, 28.57%) and non-ALI (n = 50, 71.43%) groups. Serum level of calpains in terms of calpains’ activity which was expressed as RFU per microliter and measured at beginning of CPB (baseline), 1 h during CPB, end of CPB as well as 1 h, 12 h and 24 h after CPB. Difference of serum level of calpains between 2 groups first appeared at the end of CPB and remained different at subsequent test points. Univariate and multivariate logistic regression analysis indicated that serum level of calpains 1 h after CPB was an independent predictor for postoperative ALI (OR 1.011, 95% CI 1.001 to 1.021, p = 0.033) and correlated with a lower PaO2/FiO2 ratio in the first 2 days (The first day: r = -0.389, p < 0.001 and the second day: r = -0.320, p = 0.007) as well as longer mechanical ventilation time (r = 0.440, p < 0.001), ICU length of stay (LOS) (r = 0.419, p < 0.001) and hospital LOS (r = 0. 297, p = 0.013). Conclusions: Elevated serum level of calpains correlate with impaired lung function and poor clinical outcomes, indicating serum level of calpains could act as a potential biomarker for postoperative ALI following CPB in adults.